THE DEMAND PLANNER’S SPECIAL ROLE – DEVELOPMENT PROGRAM - Mondovics, János (Advanced Logistic Systems - Theory and Practice, 2018)
The role and significance of demand planning are increasing in the operation of supply chain, in harmony of the digitalization of production and distribution. Within the corporate operation, this function collects widespread information on both the external and internal processes, interprets them and makes consensus-related decisions about the structure and scale of sales (demand) to be expected in the short term. In this regard, its performance is crucial, primarily, in relation to stocks, the use of capacities, cash flow as well as profitability. Consequently, it is of paramount importance to harmonize the organization surrounding the demand planner and the processes, which is the major goal of the described development program.